Model of Strengthening the Social Functioning of the Elderly in the Era of Society 5.0 - Firda Dwi Anjani; Denny Maulana Pratama; Hery Wibowo; Binahayati Rusyidi (UIN Sunan Kalijaga Yogyakarta, 2021)
This article aims to describe the model of strengthening social functioning in the 5.0 society era. The discussion begins by discussing the constellation of the elderly with the physical and social environment, the position of the elderly in the 5.0 society era, and social capital as a model for strengthening the social functioning of the elderly in the 5.0 society era. This study is based on a literature study with an ecological approach both physically and socially. According to the findings of this study, the physical and social environment have an impact on the social functioning of the elderly. In addition, in responding to existing opportunities, social capital can be a strength to strengthen the social functioning of the elderly in the 5.0 era of society.Keywords: Elderly, Physical and Social Environment, Society5.0, Social Functioning, Social Capital.